Penguatan fungsi kelembagaan desa (Studi kasus penggunaan dana desa di Kabupaten Gowa) - Amir Muhiddin (Seminar Nasional LP2M UNM, 2019)
This is qualitative research aimed at giving an idea of how the use of Village Funds in Je'ne Tallasa Village. Moreover, the purpose of this study is to provide a description of how the institutional functions contribute to the management of village funds in Je’netallasa Village, Gowa Regency. The technique of collecting data is through observation, in-depth interviews, and documentation. Furthermore, the subjects in this study consisted of 1) Elements of the Gowa Regency Government including the head of the government section and the head of the community empowerment and village government agency; 2) Elements of the Village Government include the village head, village secretary and village officials; 3) Elements of the Village Consultative Board (BPD) which includes the chair and the members; 4) Community elements include, community leaders, youth leaders, and traditional leaders. Data were analyzed using the Miles and Heberman (1984) analysis model with the following steps: data collection, data reduction, data display, and conclusion drawing/verification. The results of the study show that: 1) Je’netallasa Village 2015/2016 Budget Year, received village funds of Rp 338,900,000. This fund has been utilized for several development programs such as making drainage, installing pavers, rehabilitating village offices, painting and procuring mobiles and air conditioners. However, in terms of the quality of the programs mentioned above, it has not shown a positive thing as the program is considered to be less participatory and almost does not involve BPD. Besides, community empowerment has not become an important concern. Despite the fact, the essence of village funds distribution is to empower people to live independently and not always dependent on the government. 2) Institutional functions have not made a positive contribution to the management of village funds. This is due to weak organizational functions, which results in an unequal relationship between the village government and the BPD, as well as the relationship between the village government and the district government. The function of Human Resources (HR) is also weak and it results in the interventions of the district government. Hence, the programs do not actually meet the needs of the community. In addition, the regulatory functions or rules used are not supportive because they are not only well understood by the implementers in the field, but the rules often overlap and make the implementers in the field doubtful even fear of making the program.